2006
DOI: 10.1016/j.virol.2006.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent enhancement of transcription of p300 by human T-lymphotropic type 1 p12I

Abstract: Human T-lymphotropic virus type 1 (HTLV-1) p12I localizes to the endoplasmic reticulum and Golgi causing sustained release of calcium, T cell activation, and enhanced expression of several calcium-regulated genes. In recent microarray studies, p300 mRNA was increased in T cells expressing p12I. The co-activator p300 is a key regulator of cellular and viral transcription; however, factors that influence its transcriptional regulation are less well studied. We hypothesized that the transcription of p300 is calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Compared with its well‐characterized biological functions, only a very few studies have reported on its transcriptional regulation. Transcription factor early growth response 1 (Egr‐1) has been shown to regulate p300 transcription through the Egr‐1 DNA‐binding cis ‐acting elements within the p300 promoter, intracellular signaling, or viral infection or expression of viral protein (Cai et al, 2006; Nair et al, 2006; Saegusa et al, 2008; Yu et al, 2004). Meanwhile, Tat is known to alter various intracellular signaling pathways (Liu et al, 2002; Peruzzi, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with its well‐characterized biological functions, only a very few studies have reported on its transcriptional regulation. Transcription factor early growth response 1 (Egr‐1) has been shown to regulate p300 transcription through the Egr‐1 DNA‐binding cis ‐acting elements within the p300 promoter, intracellular signaling, or viral infection or expression of viral protein (Cai et al, 2006; Nair et al, 2006; Saegusa et al, 2008; Yu et al, 2004). Meanwhile, Tat is known to alter various intracellular signaling pathways (Liu et al, 2002; Peruzzi, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This may involve the translocation of ICAMs from the endoplasmic reticulum to the proteasome as opposed to its normal pathway of migrating from the endoplasmic reticulum to the Golgi and finally to the surface, similar to p12 I -mediated down-modula- I modulates the expression of various calcium-regulated genes involved in cell adhesion, presumably by modulating the expression of transcriptional regulators such as p300 (52,53). The ICAM-1 promoter contains potential binding sites for a variety of transcriptional regulatory factors, including the CRE motif that can bind to p300/CBP complex (19,70).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have revealed that p8, which localizes at the cell surface, is also capable of downregulating NFAT activity, though in a LAT-dependent manner [68]. Besides NFAT, p12 expression influences other calcium-regulated proteins, like the transcriptional coactivator p300 [69], which can in turn modulate the transcription of viral genes from the HTLV-1 LTR [70]. Moreover, p12 can promote intercellular viral spread by inducing lymphocyte function-associated antigen 1 (LFA-1) clustering on T-cells through a calcium-dependent mechanism (Fig.…”
Section: Htlv-1a Orf-imentioning
confidence: 99%